2010
DOI: 10.1111/j.1365-2982.2010.01529.x
|View full text |Cite
|
Sign up to set email alerts
|

The chemical code of porcine enteric neurons and the number of enteric glial cells are altered by dietary probiotics

Abstract: The neuronal and glial changes described here illustrate plasticity of the ENS in response to an altered luminal environment in the gastrointestinal tract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 36 publications
4
35
0
1
Order By: Relevance
“…Changes in the cellular profile area of enteric neurons can occur in response to changes in the lumen of the GIT (Giancamillo et al 2010). Our results indicate that FR reduced the area of the cellular profile of myenteric neurons in the proximal colon, which is consistent with results obtained in segments of the large intestine (Sant'Ana et al 1997, Castelucci et al 2002 and small intestine (Torrejais et al 1995, Natali et al 2003 in undernourished rats during pregnancy, lactation, and adulthood.…”
Section: Discussionsupporting
confidence: 91%
“…Changes in the cellular profile area of enteric neurons can occur in response to changes in the lumen of the GIT (Giancamillo et al 2010). Our results indicate that FR reduced the area of the cellular profile of myenteric neurons in the proximal colon, which is consistent with results obtained in segments of the large intestine (Sant'Ana et al 1997, Castelucci et al 2002 and small intestine (Torrejais et al 1995, Natali et al 2003 in undernourished rats during pregnancy, lactation, and adulthood.…”
Section: Discussionsupporting
confidence: 91%
“…Kamm et al (2004) have reported that the numbers of neurons containing calbidin, which is a multiple calcium binding protein, decreased in jejunum of pigs supplemented with Sacharomyces boulardii. Similarly Giancamillo et al (2010) have reported that the density of galaninergic and calcitonin gene-related peptide (CGRP) positive neurons increased in submucosal plexus of ileum of Pediococcus acidilactici treated pigs. Galanin is effective on peristaltic activity, secretion, blood flow and eating behaviors, and CGRP is effective on the modulation of sensory functions and the regulation of activity of smooth muscle.…”
Section: Probiotics and Enteric Nervous Systemmentioning
confidence: 99%
“…The impact that changes in microbiota can have on enteric circuitry is highlighted by the effects of probiotics on the chemical coding of enteric neurons. Piglets on a diet supplemented with the probiotic Saccharomyces boulardii showed reduced numbers of calbindin + neurons (118), while those fed with Pediococcus acidilactici had an increased number of CGRPand galanin-expressing neurons in the submucosal ganglia of the ileum (119). Interestingly, the probiotic Lactobacillus paracasei was shown to attenuate visceral hypersensitivity induced by the perturbation of gut microbiota with antibiotics (120).…”
Section: Microbiota Influence On Ens Developmentmentioning
confidence: 99%